Hypomethylation of the CTGF gene locus is a common feature of paediatric pre-B acute lymphoblastic leukaemia - Welch, Mathew; Greene, W.; Kees, U. (Blackwell Science Ltd, 2013)
The connective tissue growth factor gene (CTGF) is aberrantly expressed in 75% of precursor B-cell acute lymphoblastic leukaemias (pre-B ALL) and is associated with poor outcome. We identified consistent hypomethylation of the CTGF locus in primary pre-B ALL specimens regardless of CTGF expression. By contrast, primary T-cell ALL specimens, which do not express CTGF, exhibited distinctive patterns of hypermethylation. Furthermore, we confirmed that global changes in DNA methylation and histone acetylation can both functionally modulate CTGF expression in pre-B ALL cell lines. These data suggest that hypomethylation of the CTGF locus is an essential prerequisite for aberrant CTGF expression in pre-B ALL.